Jungermannia obliquifolia (Schiffn.) VÁNA (Marchantiophyta) from India - Manju, C. N.; Rajesh, K. P.; Madhusoodanan, P. V. (Bangladesh Journal of Plant Taxonomy, 2009)
Not available. Keywords: Marchantiophyta; Jungermannia obliquifolia; New record; Western Ghats; India. DOI: 10.3329/bjpt.v16i1.2752 Bangladesh J. Plant Taxon. 16(1): 95-97, 2009 (June)